La regulación política de la publicidad sobre el alcohol y su repercusión en la percepción de las campañas publicitarias - Couderchon, Patricia (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2008)
This paper is meant to show how the French Evin law with its legal measures against alcoholism has had a direct impact on the way of carrying out advertising campaigns concerning alcoholic drinks, and has been a standing mark between two periods of the 20th century. The law has introduced a clear distinction between the «incentive» and the «informing» when it comes to estimating an advertising campaign, which distinction is used by courts when they have to decide if some advertisements for alcoholic drinks should be banned because they are considered to be ‘«incentive». A poll carried out among 209 people, based on a real case of censorship, has assessed the way consumers appreciate such a clear distinction and emphasized the fact that the law should be changed so that it should be more in keeping with what consumers actually appreciate. The poll has pointed out a mixed appreciation described in this paper, which might permit indeed to make the law tuned to the actual appreciation of consumers regarding advertising messages, while safeguarding the interests of both advisers and those the Evin law means to protect, linked to social order and the protection of high-risk sectors.
Keywords: Incitement; Informative; Alcoholic drinks; Positioning; Image